6(-6)=-3(x+3)

Simple and best practice solution for 6(-6)=-3(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-6)=-3(x+3) equation:



6(-6)=-3(x+3)
We move all terms to the left:
6(-6)-(-3(x+3))=0
We add all the numbers together, and all the variables
-(-3(x+3))-36=0
We calculate terms in parentheses: -(-3(x+3)), so:
-3(x+3)
We multiply parentheses
-3x-9
Back to the equation:
-(-3x-9)
We get rid of parentheses
3x+9-36=0
We add all the numbers together, and all the variables
3x-27=0
We move all terms containing x to the left, all other terms to the right
3x=27
x=27/3
x=9

See similar equations:

| 7/u=13/11 | | y=0.25(350)+20 | | 7(6x+3)=42x-10 | | 9x+27=-8 | | 11=b/20 | | 4/7=p/21 | | y=0.25(300)+20 | | 4/7=p=21 | | (4x+40)+(6x-10)=180 | | 27x-3=10 | | 300=0.25x+20 | | 8(3x-8)-10x+4=-18 | | (4x+20)+(6x-10)=180 | | 40+3x+(5x-10)=180 | | 7-3(5t-10=67 | | 6q+-1=-1q+20 | | 40+3x+5x-10=180 | | 4x+20+6x-10=180 | | 3(5c-6)=5(3c+6) | | a+7=2a−8. | | 0.5(9x+18)=-1.5(5x)-2(3+4.5) | | (3x+15)+(x+25)=180 | | 0.5(4x+2)=-2(2x+3)-11 | | -36=-6(f+-8) | | 7x+6(x+8)=22 | | 9=3/5u | | 4(f-68)=68 | | 82-v=295 | | 4x-7x+21=36 | | 4w+4(w-7)=20 | | 6u/5=30 | | (x+4)(5x+1)=0 |

Equations solver categories